1975
DOI: 10.1073/pnas.72.6.1989
|View full text |Cite
|
Sign up to set email alerts
|

Third component of complement (C3): structural properties in relation to functions.

Abstract: The third component of complement (C3) fulfills a pivotal role in the functions of the complement system. We have investigated the topological relationships among its polypeptide chains, physiologic fragments, enzyme attack regions, and functional sites. C3 consists of two chains (a and ,6) which are linked by disulfide bonds and noncovalent forces and which have molecular weights of, respectively, 120,000 and 75,000. C3 is activated by action of C3 convertase on the a-chain. With hydrolysis of one polypeptide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
51
1

Year Published

1977
1977
1989
1989

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(57 citation statements)
references
References 28 publications
5
51
1
Order By: Relevance
“…The radiolabeled C3 protein produced in vitro had the approximate molecular weight and subunit structure of purified human serum C3. The estimates of molecular size of intact C3 (both the purified serum C3 and that produced in vitro) were somewhat different from that (190,000) reported in the literature (23). This difference was not observed in analysis of the a-and ,3-subunits, the sizes of which corresponded closely to published figures (a-chain 120,000; /-chain 75,000) (23).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The radiolabeled C3 protein produced in vitro had the approximate molecular weight and subunit structure of purified human serum C3. The estimates of molecular size of intact C3 (both the purified serum C3 and that produced in vitro) were somewhat different from that (190,000) reported in the literature (23). This difference was not observed in analysis of the a-and ,3-subunits, the sizes of which corresponded closely to published figures (a-chain 120,000; /-chain 75,000) (23).…”
Section: Discussionsupporting
confidence: 58%
“…The estimates of molecular size of intact C3 (both the purified serum C3 and that produced in vitro) were somewhat different from that (190,000) reported in the literature (23). This difference was not observed in analysis of the a-and ,3-subunits, the sizes of which corresponded closely to published figures (a-chain 120,000; /-chain 75,000) (23). Since the size ofintact C3 exceeded that of the largest marker protein, a precise estimate of its molecular weight could not be determined under nonreducing conditions.…”
Section: Discussioncontrasting
confidence: 46%
“…The Mr of a2M and the a-chain of C3 were -185,000 (25) and -110,000 (26), respectively, and were distinct from p168 and p125 (data not shown). Immunoprecipitation of a2M, C3, and C4 from a human hepatoma cell line known to synthesize and secrete these three molecules (27) also revealed that p168 and p125 are not C3 or a2M (see below).…”
Section: Resultsmentioning
confidence: 99%
“…From previous studies it was concluded that proteolytic cleavage of the a'-chain of C3b (36,37) by C3bINA splits the molecule into the immunochemically defined fragments C3c and C3d (38). Our results indicate that in complete absence of/31H, C3bINA does not cleave C3b in solution (Fig.…”
Section: "mentioning
confidence: 99%